HUBUNGAN KUALITAS PELAYANAN TAMAN PENITIPAN ANAK (TPA) DENGAN TINGKAT TUMBUH KEMBANG ANAK - Sri " ramadhona; Oswati " Hasanah; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Daycare is a service which provide child care aged of 0 to 6 years old. Daycare as an alternative care have responsibility to give qualified services to optimize child growth and development. The aim of this research was to identify correlation between quality of daycare service with level of child growth and development. This research used descriptive correlation design with cross sectional approach. Respondent in research was 23 daycares and 182 children at Tampan sub-district, was taken with proportional stratified random sampling techinique, quality of daycare was evaluated using observation sheets, child growth evaluated by measure the weight and height and child development evaluated with DenverII test. Result showed that there was no correlation between quality of daycare service with level of child growth p value (0,887) > α=(0.05) but there is a correlation between quality of daycare service with level of child development p value (0,001 < α=(0.05)). Based on this research, recommended to caretakers to do more optimal stimulation to childs to improve their growth and development. Keyword: Child growth and development, daycare,quality of services